2021
DOI: 10.1111/1467-8578.12365
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of students with visual impairments in higher education: barriers and facilitators

Abstract: This study explored the factors that facilitate and complicate the higher education process for students with visual impairments (VI). The participants were six university students with VI and eight academics/ faculty members who instruct these students together with other students. Data were collected through semi-structured interviews and were analysed using content analysis methods. The students with VI stated that they face barriers related to lack of materials, difficulty obtaining lecture notes, poor aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…For instance, the findings presented here had a few similarities with Douglas and Hewett’s (2014) study, in which they revealed that personal characteristics were identified by young people with vision impairment as an enabler for contributing to their independence. As another example, in relation to barriers that were identified in this study, the findings supported previous research findings which suggested others’ attitudes as one of substantial barriers to independence of young people with vision impairment (Bishop & Rhind, 2011; Firat, 2021; Simui et al, 2018). However, this study particularly illustrated that attitudes of teachers and parents, including teachers’ low expectation and overprotective attitudes of parents, have been identified as external barriers to independence of young people with vision impairment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For instance, the findings presented here had a few similarities with Douglas and Hewett’s (2014) study, in which they revealed that personal characteristics were identified by young people with vision impairment as an enabler for contributing to their independence. As another example, in relation to barriers that were identified in this study, the findings supported previous research findings which suggested others’ attitudes as one of substantial barriers to independence of young people with vision impairment (Bishop & Rhind, 2011; Firat, 2021; Simui et al, 2018). However, this study particularly illustrated that attitudes of teachers and parents, including teachers’ low expectation and overprotective attitudes of parents, have been identified as external barriers to independence of young people with vision impairment.…”
Section: Discussionsupporting
confidence: 89%
“…There is an increased interest in investigating enablers and barriers to educational and social participation and independence of learners with vision impairment. Regardless of different national contexts, the relevant literature illustrates that other people’s attitudes towards individuals with vision impairment (Bishop & Rhind, 2011; Frank et al, 2020; Simui et al, 2018) and access to visual information (Douglas et al, 2011; Firat, 2021; Hewett et al, 2017) have been identified as widespread barriers to independence and participation of learners with vision impairment. With respect to enablers to independence and participation, the literature implies that young people with vision impairment commonly tend to identify their personal characteristics, such as maturity and self-motivation, as one of significant enablers to participation within educational and social contexts (Douglas & Hewett, 2014; Firat, 2021; Işlek, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has predominantly centred on two types of disabilities, namely hearing impairments and visual impairments. Frat (2021) indicates that students with visual impairments face significant barriers in their higher education experiences. Odame (2019) found that graduates with visual impairments encounter numerous challenges during their university studies, including inaccessible programs, lack of sufficient funding, inadequate teaching materials, physically inaccessible environments, negative attitudes from instructors, and overreliance on peers.…”
Section: College Students With Disabilitiesmentioning
confidence: 99%